Performance of a Single Layer of Clothing or Gloves to Prevent Dermal Exposure to Pesticides. Issue 3 (20th February 2020) - Spaan, Suzanne; Glass, Richard; Goede, Henk; Ruiter, Sander; Gerritsen-Ebben, Rianda
Abstract: The suitability, availability, and use of protective clothing are critical factors determining the actual dermal exposure (ADE) of operators and workers to pesticides. A realistic assessment of occupational exposure to pesticides requires information about the performance of protective clothing during everyday use. In this study, the performance of clothing or gloves has been investigated based on available dermal exposure data in order to provide recommendations for default protection factors that can be used in regulatory exposure assessments. Suitable dermal exposure data from available exposure databases were collated and analysed. The data that met the selection criteria for the analysis of the performance of protective clothing comprised studies in which protective clothing like cotton coveralls, cotton clothing, polyester–cotton coveralls, Sontara coveralls, Tyvek coveralls, butyl/neoprene gloves, latex/PE/vinyl/PVC gloves, or nitrile gloves were worn. Based on available potential and ADE levels, the migration of pesticides through this protective clothing was estimated. Evaluation of exposure data showed that on average only 2.3–2.6% of the pesticides present on the outside of the clothing or gloves migrated through the garments, although there was a large variation with migration up to 99%. Forearms, legs, and chest areas of the clothing tended to have the greatest migration of pesticides. Caution is needed in the selection of the appropriate protection offered protective clothing for specific situations. This study gives valuable information on the performance of protective clothing, for use in exposure assessment and for default setting in exposure modelling, taking into account the type of clothing or gloves worn. As new data become available, it may be possible to further refine the protection factors offered by different types of clothing or gloves, particularly where a common protocol has been used.